2012
DOI: 10.1200/jco.2010.33.4631
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Deficits in Overall Quality of Life and Non–Small-Cell Lung Cancer Survival

Abstract: A B S T R A C T PurposeEvidence has suggested a clinically meaningful relationship between self-reported quality of life (QOL) of a patient with cancer at the time of receiving a cancer diagnosis and overall survival (OS). This study evaluated the prognostic value of QOL assessments with regard to OS in a large cohort of patients with lung cancer. Patients and MethodsA total of 2,442 patients with non-small-cell lung cancer were observed between 1997 and 2007 and completed a single-item measure of overall QOL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 58 publications
7
129
0
1
Order By: Relevance
“…Furthermore, those who quit smoking develop fewer radiation pneumonitis and infections during radiotherapy, and better response to chemotherapy and targeted therapy [8,9]. Smoking cessation is associated with improved pulmonary function, weight gain, and better quality of life [10].…”
Section: Original Researchmentioning
confidence: 99%
“…Furthermore, those who quit smoking develop fewer radiation pneumonitis and infections during radiotherapy, and better response to chemotherapy and targeted therapy [8,9]. Smoking cessation is associated with improved pulmonary function, weight gain, and better quality of life [10].…”
Section: Original Researchmentioning
confidence: 99%
“…A recent paper by (Sloan et al , 2012) demonstrated in NSCLC patients that overall HRQoL measured by a simple, single item at the time of diagnosis is a significant prognostic factor for survival. However, few studies have investigated the added value of change in HRQoL from baseline over time (Eton et al , 2003; Gupta et al , 2012).…”
mentioning
confidence: 99%
“…The rural advantage in survival could also be attributable to unobserved characteristics which stem directly from living in a rural area, such as the therapeutic value of nature,36 higher quality of life37 and lower anxiety 38 39. A previous study by the authors has shown that rural patients with cancer in Ireland have a higher quality of life,40 which has been shown to be an important prognostic factor 41 42…”
Section: Discussionmentioning
confidence: 99%